Reference Points and Effort Provision - Johannes Abeler; Armin Falk; Lorenz Götte; David Huffman (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2011)
A key open question for theories of reference-dependent preferences is what determines the reference point. One candidate is expectations: what people expect could affect how they feel about what actually occurs. In a real-effort experiment, we manipulate the rational expectations of subjects and check whether this manipulation influences their effort provision. We find that effort provision is significantly different between treatments in the way predicted by models of expectation-based reference-dependent preferences: if expectations are high, subjects work longer and earn more money than if expectations are low.
urn:nbn:de:bvb:19-epub-13196-2
Keywords: C91; D01; D84; J22; 330; Reference Points; Expectations; Loss Aversion; Disappointment; Experiment; Leistungsmotivation; Erwartungstheorie; Präferenztheorie; Risikoaversion; Verlust; Test